5′-fluoro(di)phosphate-labeled oligonucleotides are versatile molecular probes for studying nucleic acid secondary structure and interactions by (19)F NMR - Baranowski, Marek R (Nucleic Acids Res, 2020)
The high sensitivity of (19)F nucleus to changes in the chemical environment has promoted the use of fluorine-labeled molecular probes to study structure and interactions of nucleic acids by (19)F NMR. So far, most efforts have focused on incorporating the fluorine atom into nucleobase and ribose moieties using either monomer building blocks for solid-phase synthesis, or nucleoside triphosphates for enzymatic synthesis. Here, we report a simple and efficient synthesis of 5′-fluoromonophosphorylated and 5′-fluorodiphosphorylated oligodeoxyribonucleotides, which combines solid-phase and in-solution synthesis methods and requires only commercially available nucleoside phosphoramidites, followed by their evaluation as (19)F NMR probes. We confirmed that the fluorine atom at the oligonucleotide 5′ end did not alter the secondary structure of DNA fragments. Moreover, at the same time, it enabled real-time (19)F NMR monitoring of various DNA-related biophysical processes, such as oligonucleotide hybridization (including mismatch identification), G-quadruplex folding/unfolding and its interactions with thrombin, as well as formation of an i-motif structure and its interaction with small-molecule ligands.